Intrinsic and Tumor Microenvironment-Induced Metabolism Adaptations of T Cells and Impact on Their Differentiation and Function - Kouidhi, Soumaya; Noman, Muhammad Zaeem; Kieda, Claudine; Elgaaied, Amel Benammar; Chouaib, Salem (Frontiers in Immunology, 2016)
It is well recognized that the immune system and metabolism are highly integrated. In this context, multilevel interactions between metabolic system and T lymphocyte signaling and fate exist. This review will discuss different potential cell metabolism pathways involved in shaping T lymphocyte function and differentiation. We will also provide a general framework for understanding how tumor microenvironmental metabolism, associated with hypoxic stress, interferes with T-cell priming and expansion. How T cell metabolism drives T cell–mediated immunity and how the manipulation of metabolic programming for therapeutic purposes will be also discussed.